2011
DOI: 10.1007/s10144-011-0281-6
|View full text |Cite
|
Sign up to set email alerts
|

Positive and negative impacts of insect frass quality on soil nitrogen availability and plant growth

Abstract: Frass deposition to soil is an important pathway by which herbivorous insects impact decomposition and soil nutrient availability. However, little is known about how frass quality influences ecosystem properties. Here, we examined the effects of frass quality on the decomposition process, soil nitrogen (N) availability, and plant growth, using frass of Mamestra brassicae (L.) that fed on fertilized or unfertilized Brassica rapa L. var. perviridis Bailey. The frass quality was largely dependent on the host plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(83 citation statements)
references
References 33 publications
6
77
0
Order By: Relevance
“…Arctic tundra vegetation is generally nutrient limited (cf. Chapin and Shaver 1985) and larvae faeces and carcasses can provide a nutrient pulse to the system (Kagata and Ohgushi 2012). Also, reduced plant nutrient uptake during 2011, as a consequence of reduced growth, may have resulted in excess nutrient availability in the following years.…”
Section: Discussionmentioning
confidence: 99%
“…Arctic tundra vegetation is generally nutrient limited (cf. Chapin and Shaver 1985) and larvae faeces and carcasses can provide a nutrient pulse to the system (Kagata and Ohgushi 2012). Also, reduced plant nutrient uptake during 2011, as a consequence of reduced growth, may have resulted in excess nutrient availability in the following years.…”
Section: Discussionmentioning
confidence: 99%
“…Indirect effects of herbivores have been long recognized for vertebrate herbivores in the tundra (Hik and Jefferies , Van der Wal et al ); herbivore faeces return nutrients to the ecosystem by providing highly decomposable resources that are rich in labile nutrients, and can enhance compensation mechanisms in plants (Gillespie et al ). Faeces of invertebrate herbivores (frass) are rapidly decomposed (Kagata and Ohgushi ) and, even small frass additions, can have a relevant impact on nutrient cycling (Frost and Hunter ). The possibility of frass of non‐outbreak invertebrate herbivores creating a positive feedback to nutrient cycling in tundra ecosystems and how this relationship might be affected by temperature need to be explored further.…”
Section: Discussionmentioning
confidence: 99%
“…Kagata and Ohgushi (2012) found that the decomposition of frass in the soil is an important pathway by which herbivorous insects impact decomposition and soil nutrient availability. In Thailand, A. domesticus and G. bimaculatus farmers report that the frass is beneficial to their rice fields (Halloran 2014, unpublished data).…”
Section: Waste Management and Nutrient Recyclingmentioning
confidence: 99%